2015
DOI: 10.1177/0735633115585928
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of an Anonymous Recipient

Abstract: This study developed a game simulation based on problem solving in the management of urban waste. We then investigated the factors affecting the decisions made by players. During gameplay, the players sought to guide the development of a city via management strategies involving a balance of economic growth and environmental protection. Nature served as an anonymous recipient of the pollution caused by the actions of players. Within a very limited time period, the players had to determine the degree to which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Games are suitable for sustainability-related foundational courses offered in K-12, as well as for programmes offered in higher education (Bell, 2016), because they are different from conventional teaching models which merely provide cognitive knowledge about environmental issues (Hungerford & Volk, 1990). Several studies have shown that games are effective in producing attitude and behaviour changes towards the environment (Knol & De Vries, 2011;Nordby et al, 2016;Tan & Biswas, 2007;Wu & Huang, 2015;Yang, Chien, & Liu, 2012). These studies are discussed in the following sections.…”
Section: Games As a Pedagogical Tool For Transforming Attitudes And Bmentioning
confidence: 99%
See 4 more Smart Citations
“…Games are suitable for sustainability-related foundational courses offered in K-12, as well as for programmes offered in higher education (Bell, 2016), because they are different from conventional teaching models which merely provide cognitive knowledge about environmental issues (Hungerford & Volk, 1990). Several studies have shown that games are effective in producing attitude and behaviour changes towards the environment (Knol & De Vries, 2011;Nordby et al, 2016;Tan & Biswas, 2007;Wu & Huang, 2015;Yang, Chien, & Liu, 2012). These studies are discussed in the following sections.…”
Section: Games As a Pedagogical Tool For Transforming Attitudes And Bmentioning
confidence: 99%
“…But in the virtual environment of games, players can test their ideas in a safe zone, try alternatives and not be afraid of making mistakes (Knol & De Vries, 2011). The realworld scenarios in games enable learners to view the consequences of their actions immediately (Wu & Huang, 2015), which gives meaningful practice before they face the real action (Butler, 1988). 'Knowledge of ecological processes and situations can influence hearts and minds, but concrete change plans are more effective at changing muscles', stated Arbuthnott (2009, p. 155), referring to the three components of attitude, namely, cognitive, affective and behavioural.…”
Section: Characteristics Of Dgbl For Esementioning
confidence: 99%
See 3 more Smart Citations